Dermal Autograft Using Donor Breast as Alternative to Acellular Dermal Matrices in Tissue Expander Breast Reconstruction: A Comparative Review. (June 2017) - North, William Darden; Kubajak, Christopher S.; St. Martin, Brad; Rinker, Brian
Abstract : Background: Shifting preference for implant-based breast reconstruction has resulted in an increased use of acellular dermal matrix (ADM) in tissue-expander breast reconstruction. The benefits afforded by ADM must be weighed against a potential increased risk for postoperative complications. Dermal autograft–assisted breast reconstruction using autograft harvest from the lower abdomen has been shown to result in equivalent aesthetics and patient satisfaction compared with ADM at a lower cost, with fewer complications. The purpose of this study was to review a series of patients who underwent bilateral mastectomy and immediate dermal autograft–assisted tissue expander (TE) breast reconstruction using the non-cancerous breast as a donor site, comparing the outcomes with a concurrent cohort of patients undergoing ADM-assisted reconstruction to determine the relative safety, cost, and effectiveness of the 2 procedures. Methods: The study population included all patients who underwent dermal autograft–assisted TE breast reconstruction, using the contralateral cancer-free breast as the source of dermal autograft, between 2010 and 2015. The ADM cohort consisted of patients who underwent bilateral mastectomy and immediate ADM-assisted TE breast reconstruction during the same period. Univariate analysis was performed for demographic data, complications, operative cost, and operative time. Data were compared using the Wilcoxon rank sum test for nonparametric data and χ 2 analyses for continuous and categorical variables. Significance was defined as P value less than 0.05. Results: Seventeen patients received dermal autograft using the non-cancerous breast donor site. Twenty-seven patients who underwent ADM-assisted reconstruction during the same period were identified. Significantly higher cost was demonstrated between groups (ADM, US 9999.87; autograft, US 3924.19; P < 0.0001). No significance difference existed operative time (autograft, 97 min; ADM, 120 min). No difference was found in wound healing complications (ADM, 14.8%; autograft, 23.53%; P = 0.47). No significant difference was found in major complications (ADM, 26%; autograft, 17.65%; P = 0.52) or infectious complications (ADM, 26%; autograft, 17.65%; P = 0.52). Conclusions: Dermal autograft–assisted breast reconstruction using the contralateral non-cancerous breast as the source of dermal autograft harvest represents a lower cost alternative to ADM without increased risk of postoperative complications.